Proceedings 2003 IEEE/RSJ International Conference on Intelligent Robots and Systems (IROS 2003) (Cat. No.03CH37453)
DOI: 10.1109/iros.2003.1249698
|View full text |Cite
|
Sign up to set email alerts
|

A deformable model-based visual system for mobile robot topologic navigation

Abstract: Deformable models have been intensively studied in image analysis through the last decade, and are used for detection and recognition of flexible or rigid templates under diverse viewing conditions. Genetic Algorithm (GA) based deformable models are used for generic visual landmark detection and interpretation. The developed system allows topologic localization and navigation using natural and artijicial landmarks, exploiting deformable models' ability for handling landmark perspective vmiaiions.The rwlting pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“…A topological representation is based on an abstraction of the environment in terms of discrete places (landmarks) with edges connecting them. In [76], present an example of this topological representation, where after of delimited region of interest, used a GA for the landmark search through the image.…”
Section: Map Representation Methodsmentioning
confidence: 99%
“…A topological representation is based on an abstraction of the environment in terms of discrete places (landmarks) with edges connecting them. In [76], present an example of this topological representation, where after of delimited region of interest, used a GA for the landmark search through the image.…”
Section: Map Representation Methodsmentioning
confidence: 99%
“…In other work, landmarks are used to define topological locations in the world. For example, Mata et al demonstrated a system for topological localization using distinctive image regions [14].…”
Section: Related Workmentioning
confidence: 99%
“…Existem diversos trabalhos sobre técnicas de criação de mapas topológico na literatura como (Kuipers e tai Byun, 1991), (Mataric, 1990) e (Mata et al, 2003). Em (Thrun et al, 1998b) é apresentado um método para conversão dos mapas métricos em mapas topológicos, resultando em representações mais compactas.…”
Section: Mapas Topológicosunclassified